Strategi Peningkatan Kompetensi Pedagogik dan Profesional Guru MI Melalui Supervisi Akademik Kepala Madrasah - Muh. Nurul Wathani (Universitas Islam Negeri Mataram, Indonesia, 2020)
The purpose of this research is to analyze and describe the implementation of academic supervision of madrasah principals as supervisors, obstacles and solutions offered in the implementation of academic supervision, and the implications of the academic supervision activities. This research was carried out through field research using a qualitative method and a phenomenological approach to a multi-site case study. Data mining techniques are observation, interview and documentation. Data analysis is through reduction, display and verification, while data validity is tested through perseverance of observation and triangulation. The results of this thesis study show that: 1) The urgency of the implementation of adakamic supervision by the heads of madrasas KKM members in improving pedagogical and professional competence of MI Riadlul Jannah NW Penjor as a KKM program departs from the results of the analysis of the need to improve teacher professionalism. This is also reinforced by a number of inhibiting factors experienced by teachers in the process of learning activities in class. 2) The implementation of the academic supervision of madrasa principals through role exchange techniques in enhancing the pedagogical and professional competence of MI Riadlul Jannah NW Penjor teachers is done through planning, implementing and evaluating activities. 3) Implications for the academic supervision of madrasa head of role-changing techniques for MI Riadlul Jannah NW Penjor are broadly divided into two parts, namely the beneficial implications for the development of institutions or madrassas providing supervision, and also the positive implications for teachers in developing pedagogical and professional competencies. Tujuan diadakannya penelitian ini untuk menganalisis dan mendeskripsikan tentang implementasi supervisi akademik para kepala madrasah selaku supervisor, hambatan dan solusi yang ditawarkan dalam pelaksanaan supervisi akademik, dan implikasi dari kegiatan supervisi akademik tersebut. Penelitian ini dilaksanakan melalui kajian di lapangan (field research) menggunakan metode kualitatif dan pendekatan fenomenologis studi kasus multisitus (multysite case study). Penggalian data dengan teknik observasi, wawancara dan dokumentasi. Analisis data melalui reduksi, displai dan verifikasi, sedangkan uji keabsahan data melalui ketekunan pengamatan dan triangulasi. Hasil penelitian tesis ini menunjukkan bahwa: 1) Urgensi pelaksanaan supervisi adakamik oleh para kepala madrasah anggota KKM dalam peningkatan kompetensi pedagogik dan profesional guru MI Riadlul Jannah NW Penjor sebagai sebuah program KKM berangkat dari hasil analisis kebutuhan peningkatan profesionalisme guru. Hal ini diperkuat juga dari sejumlah faktor penghambat yang dialami oleh guru dalam proses kegiatan pembelajaran di kelas. 2) Implementasi supervisi akademik kepala madrasah melalui teknik tukar peran dalam peningkatan kompetensi pedagogik dan profesional guru MI Riadlul Jannah NW Penjor dilakukan melalui kegiatan perencanaan, pelaksanaan dan evaluasi. 3) Implikasi supervisi akademik kepala madrasah teknik tukar peran bagi MI Riadlul Jannah NW Penjor secara garis besar terbagi menjadi dua bagian yaitu implikasi yang bermanfaat bagi pengembangan lembaga atau madrasah penyelenggara supervisi, dan juga implikasi positif bagi guru dalam mengembangkan kompetensi pedagogik dan kompetensi profesionalnya.